Produtividade e valor nutricional da forragem e de grãos de cereais de inverno conduzidos em integração lavoura pecuária com soja em sucessão - Taffarel, Loreno Egidio (2015)
Aimed to evaluate winter cereals conducted with or without grazing under installment of the nitrogen dose in relation to the components and bromatological quality of forage and grain, as well as the presence of mycotoxins in grains. In succession, it evaluated the agronomic characteristics and soybean yield. The work was carried out from 24/04/2012 to 03/21/2014. The experimental design was randomized blocks in tracks scheme, with four replications. The treatments consisted of 126 IPR oats, triticale IPR 111 and wheat BRS Tarumã in bands A (10 x 18 m) and different management in bands B (5 x 30 m): with or without grazing with 120 kg ha-1 N in coverage (two installments of 60 kg ha-1) and two grazing (three installments of 40 kg ha-1 N). The grazing were carried to a height of 15 cm. For forage characteristics, it was found that no grazing managed plants have greater height and produce higher amount of straw and forage dry matter per hectare, even considering those which have the same N coverage. In drought condition, the IPR 126 oats produces more dry matter per hectare, followed by triticale. The relationship wheat stalk leaf is greater than oat and triticale and this justifies the high crude protein content of that culture. The nutritional value of oat forage IPR 126, wheat and triticale BRS Tarumã IPR 111 are similar in the first and second grazing grazing the best nutritional value fodder is oat and wheat due to higher crude protein and digestibility and lower fiber neutral detergent fiber and acid detergent. Mature plants before harvest and with two grazing have lower height. The realization of one grazing on wheat BRS Tarumã increases the grain productivity by 25% compared to wheat not grazed. Regardless of managements, low rainfall in July and August reduces the productivity of the three cultures grains, making unfeasible the commercial production of grain and therefore an alternative can be use the whole plant for silage for animal feed. The treatments does not interfered with the digestibility of wheat grain and triticale, but reduced the fat content of these grains. The grazing reduce the nutritional value of oat grains. Environmental conditions and grazing favor the occurrence of mycotoxins in excess of the levels allowed by the legislation as food for nursing infants and children in early childhood. However, the levels of aflatoxin, fumonisin and zearalenone in grain not prevent its use in animal feed. Soybean cultivation in succession to triticale results in less height than in succession of oats or wheat, however, none winter cereal or grazing management interferes with statistical significance in plant population, thousand grain weight and crop yield. Grazing once or twice the winter cereal forages until a height of 15 cm of soil results in increased soybean yield by about 10%